Pudore e pedagogia: dalla scomparsa al ruolo “ecologico” per l’educazione e la formazione - Cosimo Di Bari (Studi sulla Formazione, 2016)
The history of childhood attributes a significat role to shame: starting from Neil Postman and other authors, philosophy, anthropology and other human sciences offer to pedagogy a description of this concept. The articles examines the ecological role of shame in pedagogy.